2021
DOI: 10.1002/cmdc.202100451
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of CF3Se‐Substituted α‐Amino Acid Derivatives

Abstract: Several CF3Se‐substituted α‐amino acid derivatives, such as (R)‐2‐amino‐3‐((trifluoromethyl)selanyl)propanoates (5 a/6 a), (S)‐2‐amino‐4‐((trifluoromethyl)selanyl)butanoates (5 b/6 b), (2R,3R)‐2‐amino‐3‐((trifluoromethyl)selanyl)butanoates (5 c/6 c), (R)‐2‐((S)‐2‐amino‐3‐phenylpropanamido)‐3‐((trifluoromethyl)selanyl)propanoates (11 a/12 a), and (R)‐2‐(2‐aminoacetamido)‐3‐((trifluoromethyl)selanyl)propanoates (11 b/12 b), were readily synthesized from natural amino acids and [Me4N][SeCF3]. The primary in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 50 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Among the fluorine-containing groups, the trifluoromethylselenyl group (CF 3 Se) is an emerging fluorinated moiety and has attracted increasing attention because it has a relatively high Hansch lipophilicity parameter (Hansch–Leo Parameter π R = 1.61) , and strong electron-withdrawing effect (Hammett constants σ m = 0.44, σ p = 0.45) , As we know, selenium (Se) is an essential trace element in the human body as a vital part of antioxidant enzymes that protect cells against the effects of free radicals produced during metabolism . Moreover, though there are no CF 3 Se-containing drugs or agrochemicals yet, recent investigations have demenstrated that trifluoromethylselenolated compounds have a great potential for application in life sciences . In this context, it is highly desirable to develop efficient methods to synthesize CF 3 Se-containing compounds as well as develop new trifluoromethylselenolation reagents …”
mentioning
confidence: 99%
“…Among the fluorine-containing groups, the trifluoromethylselenyl group (CF 3 Se) is an emerging fluorinated moiety and has attracted increasing attention because it has a relatively high Hansch lipophilicity parameter (Hansch–Leo Parameter π R = 1.61) , and strong electron-withdrawing effect (Hammett constants σ m = 0.44, σ p = 0.45) , As we know, selenium (Se) is an essential trace element in the human body as a vital part of antioxidant enzymes that protect cells against the effects of free radicals produced during metabolism . Moreover, though there are no CF 3 Se-containing drugs or agrochemicals yet, recent investigations have demenstrated that trifluoromethylselenolated compounds have a great potential for application in life sciences . In this context, it is highly desirable to develop efficient methods to synthesize CF 3 Se-containing compounds as well as develop new trifluoromethylselenolation reagents …”
mentioning
confidence: 99%
“…Recently, the trifluoromethylselenyl group is generally applied to pharmaceutical research; the relevant investigation in pesticide has been rarely reported. It has been proved that the combination of Se or SeCF 3 with bioactive molecules may improve the activity and biosafety of these compounds. The development and exploration of selenium-containing structures may provide new possibilities for the discovery of safe, efficient, and environmentally friendly pesticides (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the significant electronic characteristics (Hammett constants σ p = 0.45, σ m = 0.44) and the larger Hansch–Leo parameter (π = 1.61) than those of OCF 3 (π = 1.04) and SCF 3 (π = 1.44) groups, the SeCF 3 functionality has been recognized as one of the most privileged structural motifs in the pharmaceutical and agrochemical fields. The recent studies on a series of fresh SeCF 3 -containing bioactive compounds have further strengthened this situation. , Thus, great efforts have been made in the construction of C–SeCF 3 bonds by the development of novel SeCF 3 reagents and trifluoromethylselenolation methodologies. , It should be noteworthy that among the known SeCF 3 sources, tetramethylammonium trifluoromethylselenate ([Me 4 N]­[SeCF 3 ]) has been considered as the more convenient and versatile reagent because it is readily accessible, easy to handle, and thermally stable, possessing rich chemistry, and has contributed heavily to the preparation of diverse SeCF 3 -containing molecules. At present, the search for efficient methods for the introduction of SeCF 3 group into a wide range of organic scaffolds with [Me 4 N]­[SeCF 3 ] has attracted a great deal of attention, which would undoubtedly benefit to accelerate the practical applications of the trifluoromethylselenylated compounds.…”
Section: Introductionmentioning
confidence: 99%